EXCELLENT GERONTIC NURSING CARE FOR NY.L WITH OSTEOPOROSIS AT UPTD SOCIAL SERVICES FOR ELDERLY AGE BINJAI YEAR 2023: EXCELLENT GERONTIC NURSING CARE FOR NY.L WITH OSTEOPOROSIS AT UPTD SOCIAL SERVICES FOR ELDERLY AGE BINJAI YEAR 2023 - Hutabarat, Adelina Florensia Hutabarat; Nelli Rusmei Sitompul; Yessi Winata Hutagalung; Julius Daud Ndruru; Martaulina Sinaga; Petra Diansari Zega, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Osteoporosis is a condition in which bones become brittle and susceptible to fracture due to significant loss of bone mass and changes in bone structure. The term "osteoporosis" itself comes from Greek, where "osteo" means bone and "porous" means holes or porous. The prevalence of osteoporosis has increased significantly worldwide, with projected incidence rates increasing in the future. WHO predictions show that the number of osteoporosis sufferers is expected to reach 6.3 million people by 2035, highlighting the urgency of treating and preventing this condition. The prevalence figure reaching 19.7% of the entire population or around 3.6 million people shows the large impact of osteoporosis in Indonesia. Data shows that the prevalence of osteoporosis is higher in women compared to men in Indonesia, especially in the elderly group. This is consistent with the general pattern of osteoporosis where women are more susceptible to this condition, especially after menopause due to decreased levels of the hormone estrogen. (Suarni, 2019). From the data we collected at UPTD. Binjai Elderly Social Services, we obtained data on 189 elderly people, and data on 10 people suffering from osteoporosis at the Anyelir homestead.